Methodology of the hydrocarbon pools prognosing by the complex of geophysical data - Pilipišin, Boris; Havenzon, Irina (My University, 2008)
The proposed methodology is worked out for the aims of oil and gas geology and can be used at investigation of terrigenous, terrigenous-carbonate and carbonate sections. It can also be used at prospecting and exploration of coal, ore, diamond deposits and underground water, as well as at the solving the tasks that need the detailed knowledge of the section structure (gas storages, slide dangerous zones etc.). The methodology includes the new methods and techniques of processing and interpretation of geophysical data. It is realized as a programme-methodical complex (PMC) 'Seismocyclit' and 'AFCM' - amplitude-frequency characteristic of medium, computed according to the noise constituent of wave field. It is based on the theory of sedimentary cyclicity - lithology (the teaching about rock-formations associations) and on the assumption of discompaction and compaction zones existence (the zones of reservoirs and cap rocks development). The uniting of the known geophysical methods and techniques, which were tested by time with the worked out by us techniques of processing and interpretation have led to creation of the new instrument for geological investigations. The advantages of our methodology in comparison with the commonly used methods consist in the possibility of obtaining the new qualitative data as to geological structure of the studied areas, which permit to carry out the forecast of hydrocarbons pools.

Zaproponowana metodologia została opracowana na potrzeby geologii naftowej i gazowej i może być wykorzystana do badania części terygenicznych, terygeniczno-węglanowych i węglanowych. Może ona być także wykorzystana do poszukiwań za węglem, rudami, złożami diamentów i wód gruntowych, jak również przy rozwiązywaniu zadań wymagających dogłębnej wiedzy na temat struktury danej części (zbiorniki gazu, niebezpieczne strefy osuwisk itp.). Zaprezentowana metodologia obejmuje nowe metody i techniki przetwarzania i interpretacji danych geofizycznych. W praktyce przyjmuje to postać kompleksu programowo-metodycznego „Seismocyclit” oraz charakterystyki amplitudowo-częstotliwościowej ośrodka 'AFCM', obliczonej zgodnie ze składową hałasu pola fal. Podstawą jest teoria sedymentacyjnej cykliczności litologicznej (nauki o związkach skał i formacji) oraz założenie istnienia stref dekompakcji i kompakcji (stref rozwoju zbiornika i nadkładu skalnego). Połączenie znanych metod i technik geofizycznych, które zostały sprawdzone za pomocą opracowanych przez autorów technik przetwarzania i interpretacji doprowadziło do stworzenia nowego instrumentu do badań geologicznych. W porównaniu z innymi, powszechnie stosowanymi metodami, przedstawiona autorska metoda ma zaletę polegającą na możliwości otrzymywania nowych danych jakościowych na temat struktury geologicznej badanych obszarów, umożliwiających wykonanie prognoz dotyczących złóż węglowodorów.
Metodologia prognozowania złóż węglowodorów za pomocą zestawu danych geofizycznych
Wiertnictwo, Nafta, Gaz
Keywords: hydrocarbons; reservoir; cyclit-section; węglowodory; deposit; zbiornik; odcinek cyclit; seismolithology; złoża; sejsmolitologia; complex; kompleks